Combined laser in-situ keratomileusis and accelerated corneal cross-linking: an update. Issue 4 (July 2016) - Tomita, Minoru
Abstract : Purpose of review: The purpose is to review the literature of combined laser in-situ keratomileusis (LASIK) and accelerated corneal collagen cross-linking (CXL) in context of its indications-contraindications, kerato-refractive, visual and safety outcomes, particularly with reference to preventing the development of post-LASIK ectasia. Recent findings: LASIK + accelerated CXL has been developed with the rationale that the addition of CXL after LASIK may strengthen the LASIK compromised corneal biomechanics and minimize the complications such as post-LASIK ectasia. Different clinical studies have documented the safety and efficacy of LASIK + accelerated CXL for the correction of myopia or hyperopia and in the patients with low predicted residual bed thickness. Summary: Available literature shows that refractive and keratometric outcomes of LASIK + accelerated CXL are comparable or better than LASIK alone. Less regression has been observed after LASIK + accelerated CXL compared with LASIK alone and no case of post-LASIK ectasia development has been reported among 673 eyes with the follow-up ranging from 3 months to 4.5 years. Future studies with large numbers of patients and longer postoperative follow-ups are needed to establish the efficacy of LASIK + accelerated CXL in preventing the development of post-LASIK ectasia.